2018
DOI: 10.1155/2018/7350715
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Biodiesel Applied to the Transportation Fleets in the Greater Houston Area

Abstract: Houston, the fourth largest metropolis in the US, currently experiences severe air pollution. Major pollutants, such as VOCs, CO, NO , PM, SO , CH 4 , and CO 2 , are released from the transportation fleets. To decrease fossil fuel use and greenhouse gas emissions from fleet vehicles, more and more biodiesel is used in vehicles in the Houston metropolis. The GREET model was used for simulating the fuel cycle emissions of diesel vehicles using different biodiesel blends in Houston. The fuels examined were diesel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…CO emissions were high at the beginning of the urban cycle for all fuels due to its cold engine operation condition. Here, CO emissions at the beginning of the cycle could be suppressed as the biodiesel ratio increased due to the oxygen content of biodiesel [3][4][5][6][7][8][9][10][11]. CO emissions during the rest of the cycle were near zero except at the maximum vehicle speed of the extra-urban cycle, which reached 120 km/h, but were still low due to the DOC having reached its optimum ignition temperature [19].…”
Section: Emissions Test Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CO emissions were high at the beginning of the urban cycle for all fuels due to its cold engine operation condition. Here, CO emissions at the beginning of the cycle could be suppressed as the biodiesel ratio increased due to the oxygen content of biodiesel [3][4][5][6][7][8][9][10][11]. CO emissions during the rest of the cycle were near zero except at the maximum vehicle speed of the extra-urban cycle, which reached 120 km/h, but were still low due to the DOC having reached its optimum ignition temperature [19].…”
Section: Emissions Test Resultsmentioning
confidence: 99%
“…Hongbo Du et.al reported that biodiesel could promote a decrease in greenhouse gas (GHG) emissions. They reported that the use of B20 in a 50% diesel vehicle in the Greater Houston Area could reduce daily GHG by 712.1 CO 2 equivalent tons [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CN is also an important parameter that reflects engine performance, the generation of nitrous oxide, and the combustion of biodiesel (Islam et al, 2013.;Cho et al, 2019). Although the biodiesel properties of strain KNUA061 showed slightly higher values of IV (138-147) and lower values of than the standard values (IV: ≤120; CN: ≥47), it is still expected that the biodiesel produced from T. obliquus KNUA061 could be used as a blending resource for transportation fuels since biodiesel blends with petrodiesel have been widely used as automotive fuels worldwide (Kousoulidou et al, 2010;Salvi and Panwar 2012;Du et al, 2018). However, further studies are needed to promote biodiesel properties by changing the cultivation conditions and other biotechnological techniques.…”
Section: Discussionmentioning
confidence: 96%
“…Blends of B20 and lower than that are used in diesel engines without requiring any change in the engine design and control calibration [25]. B20 is the most common biodiesel blend, and B5 is usually used in transportation [30,31]. Biodiesels are rarely used in RCCI combustion engines as port fuel injection [32] and are often used as direct fuel injection [33,34].…”
Section: Introductionmentioning
confidence: 99%